2016
DOI: 10.1088/1674-1056/25/7/070303
|View full text |Cite
|
Sign up to set email alerts
|

Intercept-resend attack on six-state quantum key distribution over collective-rotation noise channels

Abstract: We investigate the effect of collective-rotation noise on the security of the six-state quantum key distribution. We study the case where the eavesdropper, Eve, performs an intercept-resend attack on the quantum communication between Alice, the sender, and Bob, the receiver. We first derive the collective-rotation noise model for the six-state protocol and then parameterize the mutual information between Alice and Eve. We then derive quantum bit error rate for three interceptresend attack scenarios. We observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Moreover, quantum computing can simulate complex biological systems, leading to the development of new drugs and therapies (Cao et al, 2018 ). QTs can provide secure transmission of medical data, ensuring privacy (Senekane et al, 2017 ; Senekane, 2019 ) and confidentiality (Garapo et al, 2016 ; Mafu and Senekane, 2018 ).…”
Section: Quantum Technology: Applications and Potential Driver To Del...mentioning
confidence: 99%
“…Moreover, quantum computing can simulate complex biological systems, leading to the development of new drugs and therapies (Cao et al, 2018 ). QTs can provide secure transmission of medical data, ensuring privacy (Senekane et al, 2017 ; Senekane, 2019 ) and confidentiality (Garapo et al, 2016 ; Mafu and Senekane, 2018 ).…”
Section: Quantum Technology: Applications and Potential Driver To Del...mentioning
confidence: 99%
“…Then, Wu and Chen (2015) analyzed a multi-photon analysis for the three-stage quantum protocol under the collective-rotation noise model and demonstrated that a multi-photon system provides better error rate tolerance during transmission in a noisy environment [52]. Furthermore, Garapo et al [53] investigated the influence of the intercept-resend attack on the six-state QKD over collective-rotation noise channels and found that the protocol was secure when the angle of rotation was restricted within certain bounds. This was followed by security analysis for the E91 protocol in the presence of a collective-rotation noise channel [54].…”
Section: Introductionmentioning
confidence: 99%
“…Quantum cryptography state QKD. The intercept-resend attack is approached on the quantum communication channel (Garapo et al, 2016). Another study found that the quantum error rate decreases when increasing the depolarizing parameter characterizing the noise of the channel after applying the disturbance effect of a depolarizing channel on the security of the QKD of the four-state BB84 protocol has been applied (Dehmani et al, 2012).…”
Section: Introductionmentioning
confidence: 99%